2012
DOI: 10.1161/circulationaha.112.113944
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mild to Moderate Chronic Kidney Disease With Venous Thromboembolism

Abstract: Background Recent findings suggest that chronic kidney disease (CKD) may be associated with increased risk of venous thromboembolism (VTE). Given the high prevalence of mild-to-moderate CKD in the general population, in depth analysis of this association is warranted. Methods and Results We pooled individual participant data from five community-based cohorts from Europe (HUNT2, PREVEND and Tromsø study) and United States (ARIC and CHS study) to assess the association of estimated glomerular filtration rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(54 citation statements)
references
References 39 publications
3
50
1
Order By: Relevance
“…Finally, patients with cirrhosis are at risk of developing both acute and chronic kidney disease [83][84][85][86][87]. In the general population, chronic renal disease is associated with a high thrombotic risk, while in acute renal failure the bleeding risk prevails over that of thrombosis.…”
Section: Factors Tipping the Hemostatic Balance In Cirrhosismentioning
confidence: 99%
“…Finally, patients with cirrhosis are at risk of developing both acute and chronic kidney disease [83][84][85][86][87]. In the general population, chronic renal disease is associated with a high thrombotic risk, while in acute renal failure the bleeding risk prevails over that of thrombosis.…”
Section: Factors Tipping the Hemostatic Balance In Cirrhosismentioning
confidence: 99%
“…In particular, an association between reduced estimated glomerular filtration rate (eGFR) and an increased VTE risk was found [5,8], even in the non-CKD range of eGFR [8], although other studies confirmed this association for only severe eGFR reductions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggested that chronic kidney diseases (CKD) may be associated with increased VTE risk in the general population, but conflicting results were reported [4][5][6][7][8]. In particular, an association between reduced estimated glomerular filtration rate (eGFR) and an increased VTE risk was found [5,8], even in the non-CKD range of eGFR [8], although other studies confirmed this association for only severe eGFR reductions [7].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 CKD is increasing in prevalence and is associated with an increased risk of atrial fibrillation and venous thrombosis, both of which are indications for NOAC use. 11,12 In North America, these agents have been approved by the US Food and Drug Administration and Health Canada for use in patients with varying degrees of kidney dysfunction. However, these agencies have extrapolated the efficacy and safety data from the NOAC trials and approved dabigatran and rivaroxaban for use in patients with more severe CKD, despite the exclusion of such patients from the trials (Table 1).…”
mentioning
confidence: 99%